Mild exacerbation of obesity- and age-dependent liver disease progression by senolytic cocktail dasatinib + quercetin - Raffaele, Marco; Kovacovicova, Kristina; Frohlich, Jan; Lo Re, Oriana; Giallongo, Sebastiano; Oben, Jude A; Faldyna, Martin; Leva, Lenka; Giannone, Antonino Giulio; Cabibi, Daniela; Vinciguerra, Manlio (Cell communication and signaling, 2021)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is increasingly prevalent and represents a growing challenge in terms of prevention and treatment. A minority of affected patients develops inflammation, subsequently fibrosis, cirrhosis and hepatocellular carcinoma (HCC). HCC is a leading cause of cancer-related death. An increased number of senescent cells correlate with age-related tissue degeneration during NAFLD-induced HCC. Senolytics are promising agents that target selectively senescent cells. Previous studies showed that whereas a combination of the senolytic drugs dasatinib and quercetin (D + Q) reduced NAFLD in mice, D + Q lacked efficacy in removing doxorubicin-induced β-gal-positive senescent cells in human HCC xenografted mice. Whether D + Q has an effect on the age-associated spectrum of NAFLD-inflammation-HCC remains unknown. METHODS: Here, we utilized an established model of age- and obesity-associated HCC, the low dose diethylnitrosamine (DEN)/high fat diet (HFD), a regimen promoting liver inflammation and tumorigenesis over a long period of 9 months. Four groups of mice each were created: group 1 included control untreated mice; group 2 included mice treated with D + Q; group 3 included mice undergoing the DEN/HFD protocol; group 4 included mice undergoing the DEN/HFD protocol with the administration of D + Q. At the end of the chemical/dietary regimen, we analyzed liver damage and cell senescence by histopathology, qPCR and immunoblotting approaches. RESULTS: Unexpectedly, D + Q worsened liver disease progression in the DEN/HFD mouse model, slightly increasing histological damage and tumorigenesis, while having no effect on senescent cells removal. CONCLUSIONS: In summary, using an animal model that fully recapitulates NAFLD, we demonstrate that these compounds are ineffective against age-associated NAFLD-induced HCC. Video Abstract.
Keywords: Diethylnitrosamine; Senolytics; quercetin; Aging; Quercetin; Disease Progression; Inflammation; léky proti stárnutí; Obesity; progrese nemoci; Non-alcoholic Fatty Liver Disease; Gene Expression Regulation; Disease Models, Animal; myši inbrední C57BL; mužské pohlaví; nealkoholová steatóza jater; Mice; Diet, High-Fat; dieta s vysokým obsahem tuků; regulace genové exprese; nemoci jater; stárnutí; Liver diseases; modely nemocí na zvířatech; zvířata; Dasatinib; Cancer; Senotherapeutics; Liver Diseases; obezita; myši; dasatinib; diethylnitrosamin; Mice, Inbred C57BL; Male; Animals